(untitled) (Sambahak: Human Rights Journal, 2025)
In Nepal, education is legally recognized as a fundamental human right, yet for millions of children, it remains an unrealized promise. The country’s rights-based approach (RBA), rooted in the 2015 Constitution and international conventions, envisions education as a catalyst for social justice. However, despite this progressive legal architecture, a profound gap persists between policy and practice. Employing a qualitative narrative review of secondary sources, this paper utilizes the Participation, Accountability, Non-discrimination, Empowerment, and Linkage (PANEL) (and Availability, Accessibility, Acceptability, Adaptability (AAAQ) (frameworks as analytical lenses. The study investigates how the RBA’s implementation is crippled by systemic obstacles, including chronic underfunding, entrenched socio-economic and caste-based discrimination, geographic isolation, and weak institutional capacity. These deep-seated barriers perpetuate a system where education, intended as a great equalizer, functions instead as a mechanism of exclusion, particularly for marginalized communities. This analysis argues that bridging this gap is a matter of social justice that transcends mere legal commitments. Fulfilling the right to education in Nepal requires unwavering political will to implement comprehensive reforms—including decentralized governance, robust accountability systems, and the integration of inclusive pedagogies. Ultimately, ensuring education as a fundamental right is an ethical obligation to unlock the full potential of every child in Nepal.